A pathway model for physics teachers’ pedagogical philosophy core competency development - Ze He; Lumeng Chao; Xiaofei Xue (International Journal of Evaluation and Research in Education (IJERE), 2026)
The implementation of the National Education Development Plan (2024–2035) has propelled Chinese physics education from traditional knowledge transmission toward a core competency-oriented teaching model. This transformation need to impose new demands on educationally underserved central and western regions, how teachers adapt to this shift presents an urgent challenge. This study aims to systematically analyze secondary physics teachers’ cognitive levels regarding core competencies, examine the consistency between teaching philosophies, practices, and focus on how individual teacher characteristics and external support conditions influence professional development. The sample comprised 320 secondary physics teachers from Ulanqab City, selected via stratified random sampling to ensure representativeness, with 48 teachers participated in a quasi-experimental intervention study. Findings indicate that teachers’ overall core literacy cognition levels were moderately high (M=3.86, SD=0.42), though 35.0% reached high levels. Significant differences existed across teaching experience and professional titles (p